2017
DOI: 10.21315/mjms2017.24.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Subperiosteal Drainage versus Subdural Drainage in the Management of Chronic Subdural Hematoma (A Comparative Study)

Abstract: Introduction: Symptomatic chronic subdural hematomas (CSDH) remain one of the most frequent diagnoses in current neurosurgical practice. Burr-hole craniostomy with irrigation and placement of close-system drainage is the current recommended surgery for symptomatic CSDH. The aim of this study is to perform a direct comparison between two surgical techniques in the treatment of symptomatic CSDH, which have been proven in previous studies to be efficient. Our main objective was to compare the efficacy of placemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…Parenchymal hemorrhage due to drain misplacement is a feared complication when inserting an SDD after burr hole drainage of cSDH, potentially increasing perioperative morbidity and mortality (2,7,22). All studies reporting misplacement rates showed lower rates in the SPD group (4,7,8,10,12,14). The overall misplacement rates in the included studies was 1.2% for SPD and 7.8% for SDD, while only the study by Häni et al showed a higher misplacement rate in the SPD group.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Parenchymal hemorrhage due to drain misplacement is a feared complication when inserting an SDD after burr hole drainage of cSDH, potentially increasing perioperative morbidity and mortality (2,7,22). All studies reporting misplacement rates showed lower rates in the SPD group (4,7,8,10,12,14). The overall misplacement rates in the included studies was 1.2% for SPD and 7.8% for SDD, while only the study by Häni et al showed a higher misplacement rate in the SPD group.…”
Section: Discussionmentioning
confidence: 93%
“…All studies, except one, reported on mortality rates (4,(7)(8)(9)(10)(11)(12)(13)(14). Overall mortality was lower in the SDD group, without showing significance (5.0% for SPD and 4.6% for SDD; RR 0.83, 95% CI 0.6-1.14, I 2 = 0%, z = −1.2, p = 0.25, Figure 5A).…”
Section: Mortalitymentioning
confidence: 98%
See 2 more Smart Citations
“…In 8 studies [7,10,11,14–18] including 1782 participants, the postoperative bleeding rate was statistically significant in the non-RCT group and overall effect, with RR of 4.50 (95% CI = 1.76–11.54; P = .002) and 2.39 (95% CI = 1.31–4.36; P = .004), respectively. Meanwhile, there was no significant difference in the RCT group, with RR = 1.20 (95% CI = 0.52–2.77; P = .67).…”
Section: Resultsmentioning
confidence: 99%